2016
DOI: 10.1134/s0001437016020193
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary condition of macrozoobenthos in ultrashallow zone of Taman Bay, Sea of Azov

Abstract: The distribution of macrozoobenthic communities was studied in a vast ultrashallow (0-1.2 m deep) zone of northwestern Taman Bay (separated from the Kerch Strait by Chushka spit) in 2008-2009. Fifty-two species of benthic invertebrates were recorded. The species number, as well as Shannon and Pielou diversity indices, increased along Chushka spit from base to tip. The usual inhabitants of lagoons and estuaries of the Mediterranean Basin and the open Sea of Azov dominated in benthic communities: mollusks Abra s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…1). Moreover, Pilumnus aestuarii was described from the shallow and brackish (salinity about 20‰) and highly eutrophic lagoon of Venice (Nardo, 1869) of the Adriatic Sea, which is similar to the Taman Bay of the Black Sea by the environmental conditions and the biota characteristic to for transitional waters [Spiridonov et al, 2016]. In the Adriatic and the Mediterranean Seas such lagoons characterized by lower salinity and higher eutrophication represent separate biotopes clearly different from fully saline tidally washed biotopes of the Eastern Atlantic and the NorthSea where true P. hirtellus occurs [Zariquiey Alvarez, 1968;Türkay et al, 1987;Müller, Schubart, 2007;Mavidis et al, 2009;Oliveira-Biener et al, 2010;Schubart et al, 2012;Schubart, 2014].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…1). Moreover, Pilumnus aestuarii was described from the shallow and brackish (salinity about 20‰) and highly eutrophic lagoon of Venice (Nardo, 1869) of the Adriatic Sea, which is similar to the Taman Bay of the Black Sea by the environmental conditions and the biota characteristic to for transitional waters [Spiridonov et al, 2016]. In the Adriatic and the Mediterranean Seas such lagoons characterized by lower salinity and higher eutrophication represent separate biotopes clearly different from fully saline tidally washed biotopes of the Eastern Atlantic and the NorthSea where true P. hirtellus occurs [Zariquiey Alvarez, 1968;Türkay et al, 1987;Müller, Schubart, 2007;Mavidis et al, 2009;Oliveira-Biener et al, 2010;Schubart et al, 2012;Schubart, 2014].…”
Section: Discussionmentioning
confidence: 95%
“…One of the most important factors of the high diversity and eutrophication of the Bay is the presence of extensive nearby areas occupied by macrophytes (sea grasses and algae) that create favorable conditions for the development of multi-level communities, including both periphyton and bottom zoobenthos as well as a variety of bottom sediments including all types of bottom substratum: sand, clayey silt, silt, clayey-sandy mud with high detritus content, shell rock, marl, pebbles, rocks and rocks. Accordingly, the bottoms sites in this area are represented by various biotopes with psammophilic and pelophilic communities with domination of sponges, polychaetes Nephtys cirrus, mollusks Mytilus galloprovincialis, Cerastoderma glaucum and Hydrobia, areas with hard clay outlet with predominance of burrowing bivalves Barnea candida and others [Golovkina, Nabozhenko, 2012;Biryukova et al, 2016;Spiridonov et al, 2016;Zalota et al, 2017]. In contrast, bottom communities of the outer part of the Kazachiya Bay, where crabs where collected, are represented mainly by rocky boulders or artificial hard substrates, overgrowing with various macrophytes, clusters of mussels, other fouling organisms and underlying sandy bottom at a depth of more than 10-15 m. The bay is characterized by the presence of a large number of shelters for macrofauna and zoobenthos, and a low level of sedimentation in its outer part and significantly washed into tidal cycles and during strong storms, so there is not much accumulation of organic matter and eutrophication as in the Taman Bay [e.g.…”
Section: Methodsmentioning
confidence: 99%
“…In the Taman Bay our observations indicate similar pattern of Harris mud distribution throughout the bay, although the occurrence of crabs in its extremely shallow north-western part [lacking sea grass vegetation; Spiridonov et al, 2016] is not yet confirmed.…”
Section: Distribution Of Harris Mud Crab In the Black And Azov Seasmentioning
confidence: 53%
“…Of particular interest are the early spring (8.03.2008) observations made in front of Sennoi where relatively numerous crabs have been observed at depth 3.2 m among cockles and sparse eelgrass on the grey-brown mud with a thin (about 1 cm) upper light oxygenated layer and a thick dark anoxic layer under-laid by dense shell deposits. The only area where we have not spotted R. harrisii is the very shallow (usually less than 1.5 m) north-western part of the Bay, in so called Dinskoi Bay and along the Chushka spit where extensive areas are occupied by reed [Spiridonov et al, 2016].…”
Section: Riversmentioning
confidence: 85%
See 1 more Smart Citation